Between-Frequency and Between-Ear Gap Detections and Their Relation to Perception of Stop Consonants. Issue 4 (July 2015) - Mori, Shuji; Oyama, Kazuki; Kikuchi, Yousuke; Mitsudo, Takako; Hirose, Nobuyuki
Abstract : Objectives: The objective of this study was to examine the hypothesis that between-channel gap detection, which includes between-frequency and between-ear gap detection, and perception of stop consonants, which is mediated by the length of voice-onset time (VOT), share common mechanisms, namely relative-timing operation in monitoring separate perceptual channels. Design: The authors measured gap detection thresholds and identification functions of /ba/ and /pa/ along VOT in 49 native young adult Japanese listeners. There were three gap detection tasks. In the between-frequency task, the leading and trailing markers differed in terms of center frequency ( F c ). The leading marker was a broadband noise of 10 to 20, 000 Hz. The trailing marker was a 0.5-octave band-passed noise of 1000-, 2000-, 4000-, or 8000-Hz F c . In the between-ear task, the two markers were spectrally identical but presented to separate ears. In the within-frequency task, the two spectrally identical markers were presented to the same ear. The /ba/-/pa/ identification functions were obtained in a task in which the listeners were presented synthesized speech stimuli of varying VOTs from 10 to 46 msec and asked to identify them as /ba/ or /pa/. Results: The between-ear gap thresholds were significantly positively correlated with the between-frequency gap thresholds (except those obtained with the trailing marker of 4000-Hz F c ). The between-ear gap thresholds were not significantly correlated with the within-frequency gap thresholds, which were significantly correlated with all the between-frequency gap thresholds. The VOT boundaries and slopes of /ba/-/pa/ identification functions were not significantly correlated with any of these gap thresholds. Conclusions: There was a close relation between the between-ear and between-frequency gap detection, supporting the view that these two types of gap detection share common mechanisms of between-channel gap detection. However, there was no evidence for a relation between the perception of stop consonants and the between-frequency/ear gap detection in native Japanese speakers. Abstract : To examine the relation among between-channel gap detection and the perception of stop consonants, the authors conducted an experiment to measure gap detection thresholds and identification functions of /ba/ and /pa/ in native Japanese listeners. The results showed that the between-frequency and between -ear gap thresholds were significantly correlated with each other, whereas the between-ear gap thresholds were not correlated with the within-frequency gap thresholds. The /ba/-/pa/ identification performance was not correlated with any of these gap thresholds. These results add to our understanding of commonality and separability of mechanisms underlying between-channel and within-channel gap detection and speech perception.